Cal State Hayward vs. U. C. Davis Saturday November 6, 1971 - California State College, Hayward Athletics:::::: (1971)
Program for the November 6, 1971 football game between the California State College, Hayward Pioneers and UC Davis Aggies. Includes football schedules, team rosters and probable starting lineups, photographs of CSCH players and coaches, and schedules for other CSCH sports.